Heat Transfer Analysis of Deep Coaxial Geothermal Heat Exchangers: Insights Into Heat-Flux Distribution on Borehole Wall - Ujung, Idris; A. Abdullah, Nasruddin; Suheri (Fakultas Teknik Universitas Samudra, 2025)
Briquettes are solid fuel that can be used as an alternative energy source. Making biocharcoal briquettes is one way to convert a biomass energy source into another biomass by compressing it and making it into a more regular shape. In this research, red calliandra wood was used using the pyrolysis method, temperature variations and adhesive variations. The pyrolysis temperatures used are 300°C, 400°C, and 500°C with a pyrolysis time of 60 minutes. Then the briquettes are molded with a ratio of charcoal and molasses (cane molasses) 90%:10% and 70%:30%. Briquettes are tested using the SNI 01-6235-2000 method, namely calorific value, water content, ash content and volatile matter. Of the 6 samples taken, almost all met the standards and sample A briquettes obtained the best results with a composition of 90% charcoal and 10% adhesive at a temperature of 500, producing a calorific value of 6945.67 cal/gr, water content of 6.35%, ash content of 7, 76%, volatile matter 10.81% and bound carbon 77.72%.